Signaling Рathway Blockers: Action Mechanism, Efficacy, Safety of Therapy for Patients with Psoriasis and Psoriatic Arthritis - A. A. Bakulev (State Scientific Center of Dermatovenereology and Cosmetology, 2018)
In the literature review, contemporary data on immune pathogenesis of psoriasis and the emergence of comorbid states against the background of systemic chronic inflammation among patients is discussed. On the example of the apremilast medical preparation, the information on a new class of therapeutic agents for the treatment of psoriasis and psoriatic arthritis - "small molecules" is given, including their physicochemical properties and action mechanism, as well as on the key differences from immune-suppressive and genetically engineered biological preparations. Data on large-scale international randomised clinical trials of the efficacy and safety of the PDE4 inhibitor of apremilast among patients with moderate to severe psoriasis and psoriatic arthritis is presented. The published international clinical recommendations on the use of apremilast among patients with psoriasis and psoriatic arthritis, the criteria for evaluating the response to therapy, as well as the potential profile of patients for the use of apremilast in real clinical practice are discussed.